جدلية الأمل المؤجَّل في رواية عائد إلى حيفا دراسة في إعادة تعريف الأمل بعد الصدمة التاريخية: من الخلاص إلى المواجهة : The Dialectic of Deferred Hope in Returning to Haifa, Redefining Hope after Historical Trauma: From Salvation to Confrontation - د.رابعة عمر حيات,; أ.د.حامد أشرف همداني, (Al Manhal Research Journal, 2025)
This study examines Ghassan Kanafani's novella Returning to Haifa (1969) through the analytical lens of deferred hope as a literary and philosophical concept embedded across multiple narrative, structural, symbolic, and ideological levels. The central argument posits that Kanafani radically redefines hope in the post-Nakba context, transforming it from a passive, redemptive, and deferral-based concept into an active existential stance grounded in resistance, agency, and deliberate choice. Drawing on Gérard Genette's narratological framework, Paul Ricœur's philosophy of time and memory, Cathy Caruth's trauma theory, and Frantz Fanon's liberation thought, the study traces how the novella constructs what may be termed "confrontational hope" — a mode of hoping that does not rest on the illusion of recovering what was lost, but on the acceptance of loss as a point of departure for meaningful action. The analysis proceeds through four interlocking levels: a temporal level that dismantles linear notions of recovery; a symbolic level embodied in the figure of Khaldun/Dov; an ideological level manifest in the generational conflict between Said S. Said and his son Khalid; and a human level expressed in the silent, unspeakable hope of Safiyya. The study concludes that the novella offers a rare literary model of hope that neither falsifies pain nor justifies surrender — a hope that demands full confrontation with historical truth as its sole condition of possibility.